Description of three new subspecies of Eisenia nordenskioldi (Annelida: Crassiclitellata) from Northeastern China - Qin, Mingyan; Zhao, Huifeng; Zhang, Yufeng; Han, Anne Charis N.; Shekhovtsov, Sergei V.; Wu, Donghui; Aspe, Nonillon M. (Zootaxa, 2025)
The Eisenia nordenskioldi complex is known for its high karyotype diversity and morphological type, and there are many cryptic species present in this complex. The species is widely distributed in the Palearctic biogeographic region including Northeast China. However, the taxonomy of this species complex remains inadequately defined. In our study, we examined the morphological characters of the Eisenia nordenskioldi complex in Northeast China that have not been examined before and used mitochondrial marker COI and nuclear markers ITS2, AKAP17 and FLAD1 to analyze their genetic variation. We described three new subspecies namely, E. nordenskioldi shenzi ssp. nov. E. n. jilinensis ssp. nov. and E. n. chinensis ssp. nov., which show morphological distinction and supported with molecular data. Molecular phylogenetic analyses show that the Eisenia nordenskioldi species complex is not monophyletic, supporting previous works.